Detection of qacEΔ1, qacG, qacE, qacF resistance genes in Escherichia coli producing broad-spectrum beta-lactamases to benzalkonium chloride - F Hadadi (Babol University of Medical Sciences, 2019)
BACKGROUND AND OBJECTIVE: The resistance genes of quaternary ammonium compounds(qac) play an important role in the resistance of gram-negative bacteria producing broad-spectrum beta-lactamases to disinfectants. The aim of this study was detection of qacEΔ1, qacG, qacE, qacF resistance genes in Escherichia coli producing broad-spectrum beta-lactamases to benzalkonium chloride. METHODS: This study cross sectional-descriptive was conducted on 150 clinical samples of selected hospitals in Arak. ESBL strains were identified by using phenotypic methods of disc diffusion and combinatory disc method and evaluating the SHV, TEM, CTXM1 genes by genotyping method. The PCR was performed to determine the resistance genes qacEΔ1, qacG, qacE and qacF.The electrophoresis of PCR products and the MIC of benzalkonium chloride were relative to E. coli producing ESBL. Antibiotic pattern of Escherichia coli (ESBL), quadruple ammonium resistance genes and benzalkonium chloride MIC were also investigated. FINDINGS: This study showed that 60% of Escherichia coli were ESBL producer. The qacEΔ1 genes were observed in all of them and qacE, qacF, qacG genes were not found in any of the strains. The strains had MIC range from 32 to 64 mg/l for benzalkonium chloride. Resistance to carbapenems (33.33%) was observed. CONCLUSION: This study showed that qacEΔ1 resistance gene and resistance to disinfectant benzalkonium chloride increased. Also increased resistance to the antibiotics studied were observed in E. coli ESBL strains.